Metadiscourse in the academic writing of local and international students at a university in Malaysia - Zakaria, Muhamad Khairul; Abdul Malik, Faridah; Ab. Rashid, Radzuwan; Pilus, Zahariah; Zakaria, Nur Shahida (Conscientia Beam, 2018)
This study examines the use of metadiscourse markers among 50 Malaysian and 50 Arab Pre-University students. The findings of this study indicated that there was a significant difference in the use of metadiscourse markers between Malaysian and Arab Pre-University students {χ2 (1, n = 100) = 7.17, p-value is .007} where the use of metadiscourse markers among Malaysian Pre-University students was substantially higher than that of the Arab Pre-University students. In the use of interactive markers, the results showed significant differences between Malaysian and Arab Pre-University students in the use of transitions, evidential and code glosses. Additionally, in the use of interactional markers, Malaysian and Arab students differed in their use of hedges, engagement markers and self-mentions. These variances in the frequency and forms of metadiscourse markers utilized by the students could be attributed to the diverse cultural backgrounds of the two groups of students. It is therefore suggested that English language teachers integrate and incorporate cultural elements in their lessons with regard to metadiscourse markers.